Scholarly Literature in Digital Humanities: A Comparative Analysis of Open Access and Non-Open Access Publications - M K, Sandra; M K, Sandra; Kumar A, Rupesh (International Journal of Information Studies, 2025)
Digital Humanities (DH), as a research area, has attracted the attention of scholars across the globe.  The present study attempts to trace the publication and citation trends in DH literature with a comparative analysis of Open Access (OA) and Non-Open Access (Non-OA) publications using a dataset of 3,731 publications collected from Scopus. DH literature is characterized by a steady growth from 1971 to 2024. The highest number of publications have been produced during 2022 (475).  Although a consistent increase in OA publications can be witnessed since 2009, a significant portion of DH literature (65%) is non-open access. In terms of citations, OA publications show greater potential.  Mann Whitney U test shows that the mean rank of citation counts for OA publications (2036.47) is higher than that of non-OA publications (1772.56).  The result is statistically significant (p-value=.000).  Green OA is the most preferred OA channel, with 27% of OA publications.  USA is the top contributor to DH literature with 23% of publications, while Belgium tops the list with 62% open access publication output. Computer Science (48%) is the most predominant subject area in DH.  Articles and conference papers constitute 86% of the total literature, indicating authorsâ€™ preference for scholarly communication.